2022
DOI: 10.21597/jist.991597
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Priming with β-aminobutyric acid (BABA) for Seedling Vigor in Wheat (Triticum aestivum L.)

Abstract: To achieve efficiency in seedling development, the seed must germinate quickly and homogeneously. Pre-sowing applications such as priming are practiced to eliminate or reduce the negative effects of environmental factors through germination and seedling development. This allows to reach a higher germination rate, yield, and desired plant density, especially by protecting against biotic and abiotic stresses. This study was carried out to examine the effects of pre-sowing seed applications on seedling growth and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that seed priming with BABA enhances shoot length, root length, shoot fresh weight, and root dry weight in chickpeas under salinity stress (Elradi et al, 2022). BABA priming has also been found to promote early seedling growth in bread wheat by enhancing root growth (ÖZKURT and BEKTAŞ, 2022), and to enhance the growth of Vigna radiata seedlings under NaCl/polyethylene glycol (PEG) stress (Jisha and Puthur, 2016a). Additionally, BABA priming has been shown to increase the growth of rice seedlings under both stressed and unstressed conditions (Jisha and Puthur, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that seed priming with BABA enhances shoot length, root length, shoot fresh weight, and root dry weight in chickpeas under salinity stress (Elradi et al, 2022). BABA priming has also been found to promote early seedling growth in bread wheat by enhancing root growth (ÖZKURT and BEKTAŞ, 2022), and to enhance the growth of Vigna radiata seedlings under NaCl/polyethylene glycol (PEG) stress (Jisha and Puthur, 2016a). Additionally, BABA priming has been shown to increase the growth of rice seedlings under both stressed and unstressed conditions (Jisha and Puthur, 2016b).…”
Section: Discussionmentioning
confidence: 99%